Fifth annual workshop of cytoreductive surgery for advanced ovarian cancer and peritoneal surface malignancies - Tewari, Krishnansu S. (Gynecol Oncol Res Pract, 2016)
The Fifth Annual Advanced Course in Cytoreductive Surgery for Ovarian Cancer and Peritoneal Surface Malignancies was held at and sponsored by the Division of Gynecologic Oncology at the the University of California, Irvine on Friday and Saturday, October 9-10, 2015. The workshop was comprised of didactic modules, historical treatise, an impassioned tribute, a cadaver laboratory, and heated intraperitoneal chemotherapy demonstration. This was a not-for-profit workshop, and registration fees were used to support course faculty travel to U.C. Irvine and to pay for the cadavers. The original 56 available spots were filled within three weeks of the initial announcement, prompting procurement of two additional cadavers to satisfy registration overflow and accommodate the six U.C. Irvine fellows-in-training. While international participation in the Workshops continues to rise, we have also noted more U.S.-trained Gynecologic Oncologists among the registrants.